PLANT DIVERSITY AND PHYLOGENETIC COMMUNITY STRUCTURE ALONG ENVIRONMENTAL GRADIENTS IN A TEMPERATE FOREST, SOUTH KOREA - Hyungho Kim1 Jung-Hwa Chun; Chang-Bae Lee3 (Journal of Animal and Plant Sciences, 2020)
Recently, species-centric approach in biodiversity research have been complemented by phylogenetic approach to reflect evolutionary history of species and to improve our understanding of community assembly processes in plant communities. However, the study on species and phylogenetic diversity along environmental gradients and the drivers are very rare. In this context, the present study examined species, phylogenetic diversity and phylogenetic community structures for vascular plants along two elevation transects on the Mt. Seorak, South Korea, in 2011. We calculated species richness and Faith’s phylogenetic diversity as diversity indices and net relatedness index as a phylogenetic community structure index using vegetation data from 130 plots with 400m2 in the size of each plot. We also evaluated the effects of climatic and topographic factors on the diversity patterns using multi-model inference and variation partitioning. From the results of linear regression analysis, Species richness and phylogenetic diversity have no relationship with elevation along all the study transect. However, the main factors to control these diversity patterns on the two transects were topographic factors. In addition, phylogenetic community structures showed phylogenetic overdispersion and clustering depending on the study transects, which are explained as results of biotic interactions and environmental filtering by climatic and topographic factors. These results indicate that niche-based deterministic processes such as environmental filtering and interspecific interaction may be predominant in structuring community assembly of vascular plants along local elevation gradients.
Keywords: Climatic Factor; Plant Diversity; Community Structure; Elevation; Topographic Factor